(Review Article) Identification of Endophytic Bacteria by 16S rRNA Analysis - Elfira Jumrah; Islawati, Islawati; Salnus, Subakir (Jurnal Sains dan Teknik Terapan, 2024)
16S rRNA analysis has been used for decades to identify and identify phylogenetic relationships for microorganisms, for instance bacteria. 16S rRNA analysis can identify at the genus and species level. One of the most frequently identified microorganisms using 16S rRNA analysis is endophytic bacteria. Endophytic bacteria have a symbiotic relationship with plants and can synthesis the same compounds as their hosts. The existence of endophytic bacteria benefits their hosts because it can protect plants against insects or pathogens and can help plant growth by producing plant growth regulator compounds, such as IAA, GA3, and cytokinins. In addition, some endophytic bacteria such as Bacillus Burkholderia Enterobacter species, and Staphylococcus sp have antibacterial, antioxidant and anticancer activity. Hence endophytic bacteria need to be identified molecularly. Literature studies show that endophytic bacteria have been successfully isolated from various plants such as Bacillus cereus, Baicillus pumilus, Baicillus siamensis, Burkholderia Enterobacter, and Staphylococcus sp. These endophytic bacteria have antibacterial activity, especially on pathogenic bacteria such as Klebsiella pneumonia, Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Salmonella sp.